EFEKTIVITAS PELAKSANAAN TUGAS LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) DALAM PERENCANAAN PEMBANGUNAN DI DESA BITUNURIS KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - BULELE, YOYO; PANGKEY, MASJE; ROMPAS, WELSON (Sam Ratulangi University, 2015)
ABSTRACTCommunity Empowerment is essentially a process of growth and development ofthe power of the community to be involved in various aspects of development in an areaso the end goal is the community's independence, enable and develop the ability toadvance themselves toward a better life in a balanced way.Thus in doing further researchon the effectiveness of the execution of tasks in Planning Development LPM BitunurisVillage District of Salibabu Talaud Islands. This research is qualitative, then according tothis study data analysis techniques are qualitative descriptive analysis.Based on the results it can be concluded that the effectiveness of the implementationof the LPM tasks in development planning in the Village BitunurissubdistrictSalibabuTalaud Islands is already good; in other words, the task of the LPM in rural developmentplanning in the Village District of SalibabuBitunuris Talaud Islands can be implementedquite effectively. However, further increase the available resources both human andnatural semberdaya that can be carried out in their development planning with better.Key words :Effectiviness, Task LPM, Planning Development.